Bioleaching: from natural ores to urban mines for sustainability, circularity, and carbon neutrality - Anil Kumar; Ana Teresa Lima; Gunvor M. Kirkelund; Pernille E. Jensen; Lisbeth M. Ottosen; Valerio Funari; Alan Shemi; Sehliselo Ndlovu; Helena I. Gomes (Resources, Conservation and Recycling, 2026)

Elemental content and radionuclide activity of bottom and fly ashes from Municipal Solid Waste Incineration: a time series analysis - Junaid Ghani; Katerina Rodiouchkina; Ilia Rodushkin; Enrico Dinelli; Silvia Giuliani; Luca Giorgio Bellucci; Thomas Aiglsperger; Emma Engström; Valerio Funari (Journal of Environmental Management, 2025)

Urban mining of municipal solid waste incineration (MSWI) residues with emphasis on bioleaching technologies: a critical review - Valerio Funari; Simone Toller; Laura Vitale; Rafael M. Santos; Helena I. Gomes (Environmental Science and Pollution Research, 2023)

Bioremediation of Multiple Heavy Metals Mediated by Antarctic Marine Isolated Dietzia psychralcaliphila JI1D - Janardan Ausuri; Filippo Dell’Anno; Giovanni Andrea Vitale; Fortunato Palma Esposito; Valerio Funari; Gianluigi Franci; Massimiliano Galdiero; Gerardo Della Sala; Pietro Tedesco; Daniela Coppola; Donatella de Pascale (Journal of Marine Science and Engineering, 2022)
Extreme environments host numerous microorganisms perfectly adapted to survive in such harsh conditions. In recent years, many bacteria isolated from these inhospitable environments have shown interesting biotechnological applications, including the bioremediation of polluted sites by hydrocarbons and heavy metals. In this work, we present Dietzia psychralcaliphila JI1D, a psychrophilic bacterium, isolated from Deception Island, Antarctica, which is able to resist high concentrations (up to 1000 ppm) of heavy metals and to favor their removal from polluted water systems. In detail, D. psychralcaliphila JI1D can actively promote the sequestration of arsenic, copper, and zinc from the medium up to a maximum of 31.6%, 49.4%, and 38.9%, respectively. Moreover, genome analysis allowed for the identification of heavy metal tolerance genes, thus shedding light on the mechanisms underlying the detoxification ability of the bacterium. Other than the demonstrated ability of D. psychralcaliphila JI1D to degrade polycyclic aromatic hydrocarbons, this study indicates the possibility of using this bacterium in the bioremediation of contaminated matrices, for example, those containing inorganic pollutants.